Photo-Realism : Paintings, sculpture and prints from the Ludwig Collection and others. (London : Serpentine Gallery, 1973)
De Andrea, John ; Bechle, Robert ; Close, Chuck ; Cottingham, Robert ; Eddy, Don ; Estes, Richard ; Goings, Ralph ; Stevenson Graves, Nancy ; Hanson, Duane ; Kanovitz, Howard ; McLean, Richard ; Morley, Malcolm ; Salt, John
Photo-Realism : Paintings, sculpture and prints from the Ludwig Collection and others, Serpentine Gallery, London, 4 April - 6 May 1973
boek